Occupational Stress and Associated Factors Among Administrative Employees of Colleges in Kathmandu Metropolitan City - Shampang, Galijang; Yorke, Suzana (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This study explores occupational stress and its associated demographic factors among administrative employees in Kathmandu's private colleges, addressing a critical gap in Nepal’s undergraduate education sector. Employing a quantitative research design, data were collected from 152 respondents through a structured online questionnaire comprising demographic items and the Occupational Stress Index (OSI). The primary objectives were to assess overall stress levels and determine differences based on sex, age, marital status, and educational qualification. Findings revealed OSI scores ranging from 85 to 205, with an average score of 141.26, indicating a moderate level of occupational stress. Statistical analysis using Independent Samples t-Test and One-way ANOVA showed no significant differences in stress levels based on demographic variables: sex, age, marital status, and educational qualification. This research contributes to the limited literature on workplace stress in Nepal’s higher education sector and highlights the need for institution-wide approaches to stress management. It emphasizes that organizational and contextual factors may be more influential than demographic characteristics in shaping occupational stress. The findings support the development of broad-based policies and support systems aimed at improving well-being and productivity among administrative staff.